The origin and rotation of binary asteroids - Gaftonyuk, N.; Gorkavyi, N. (Кинематика и физика небесных тел, 2005)
Binary asteroids were detected in a variety of dynamical populations, including Near-Earth Asteroids (NEAs), the main belt (MB), Trojans, and transneptunian objects (TNO). We discuss a new “multi-impact” model for origin of all classes of binary objects, including binary asteroids, Pluto–Charon, and the Earth–Moon systems. Basic elements of the model is the effective accumulation of multi-impact meteoritic ejecta in satellite orbits due to the collisional interaction between impact debris and initial low-massive ring around the primary body. The origin of satellites of all small planets in the Solar System is a result of numerous meteoritic impacts on a rotated small planet and accumulation of meteoritic ejecta around the primary body. An important prediction from the new model is that asteroids with satellites rotate faster than single asteroids. The model is confirmed by comparisons of spin rates of binary asteroids and single objects. Average spin rate for main-belt asteroid is 2.45 ± 0.05 rev/d (single objects) and 4.51 ± 0.21 rev/d (13 binary objects); direction of rotation of satellites is prograde only (three samples). Average spin rate for NEAs is 2.72 ± 0.26 rev/d (single objects) and 9.28 ± 0.25 rev/d (19 binary objects).